Brasov, City of Lost Candidacies. Case Study - Lorena Oprica (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
During 2015-2018 Brașov lost each of the three major competitions in which it participated (2020 Youth Olympic Games, 2021 European Capital of Culture, and Capital of Youths from Romania in 2019-2020). Particular aspects have drawn our attention to the processes of these candidacies and made us ask ourselves „what is Brașov” and what Brașov identifies with? This article is a short case study about how Brașov prepared its candidacy for the 2021 European Capital of Culture competition and how Brașov is perceived.